An Important Potential Anti-Epileptic/Anticonvulsant Active Group: A Review of 1,2,4-Triazole Groups and Their Action - Wang, Ying; Liu, Dachuan (Drug Research, 2021)
Epilepsy is one of the most common encountered neurological disorders. Many individuals continue to have seizures despite medical and surgical treatments, suggesting new antiepileptic/anticonvulsant drugs are required. Triazole compounds are widely used in pharmaceuticals and have gained significant importance in medicinal chemistry. This article is an attempt to systematically review the research of triazole derivatives in the design and development of anticonvulsant agents during the past two decades through extensive literature research. The results show that triazole occupy a distinct niche in heterocyclic chemistry and represent a key motif in medicinal chemistry because of their capability to exhibit an array of properties and bioactivities, Therefore, 1,2,4-triazole seems to be an important pharmacophore, especially in the field of antiepileptic, which is of great explored potentiality and utilized value. Through in-depth research on this type of structure, it is believed that more 1,2,4-triazole compounds will be developed as anti-epileptic drugs for clinical use.
Keywords: Antiepileptic Drugs; Behavioural Pharmacology; Drug Research; GABA; Chemistry